Sex has a price tag : discussions about sexuality, spirituality, and self-respect - Stenzel, Pam, 1965-; Kirgiss, Crystal (Grand Rapids, MI : Zondervan, 2003)
Provides medical facts and statistics about the consequences of sexual activity outside of marriage, biblical teachings about sexual behavior, and practical techniques for practicing abstinence.
The basics -- Boundaries -- Dealing with debt -- Physical consequences -- STDs -- Emotional consequences -- Spiritual consequences -- Choosing a personal financial advisor.
Includes bibliographical references (p. [142]).
Keywords: Chastity; Christian teenagers -- Sexual behavior; Sexual abstinence -- Religious aspects -- Christianity; Sex instruction for teenagers -- Religious aspects -- Christianity; Sex -- Religious aspects -- Christianity; Sexual abstinence; Sexual ethics; Christian life